Evaluation of Fibronectin and C-Reactive Protein Levels in Patients with Sepsis: A Case-Control Study - Mojgan Mamani; Seyyed Hamid Hashemi; Mehrdad Hajilooi; Farnaz Saedi; Amin Niayesh; Mohammad Fallah (Acta Medica Iranica, 2012)
Sepsis is a significant health problem with an estimated 750,000 new cases in the USA annually. It is also the third leading cause of death in developed countries, equaling the number of fatalities from acute myocardial infarction. The high sepsis-related mortalities mean there is an urgent need to improve the diagnosis and management of sepsis patients. The aim of this study was the evaluation of fibronectin and Creactive protein (CRP) plasma levels in patients with sepsis and other infectious diseases without sepsis. In a case-control study, 90 patients with sepsis and 90 patients with other infectious diseases without sepsis were studied. Serum levels of fibronectin and CRP were measured. The data were analyzed by SPSS version 15. The mean levels of fibronectin in the cases and controls were 288.97±89.10 mg/l and 341.24±110.53 mg/l respectively (P=0.001). The mean levels of CRP in the cases and controls were 89.42±54.05 µg/ml and 27.42±25.89 µg/ml respectively (P<0.001). Concerning the source of infection, the mean CRP levels were significantly higher in septic patients with urinary tract infection, pneumonia, and soft tissue infection (P<0.001). Decreased levels of fibronectin and increased levels of CRP may be considered as reliable diagnostic markers for sepsis. Also, CRP could be a better predictive factor for sepsis than fibronectin.